Keeping the peace in the village conflict and peacemaking in Germany, 1650-1750 - Forster, Marc R. 1959- (Studies in German history, 2024)
'Keeping the Peace in the Village' describes the nature of conflicts among rural people in the period after the Thirty Years' War. These included property disputes, conflicts between employers and their workers, disputes over marriage promises, and, most often, honour disputes